KARAKTERISTIK TOKOH PEREMPUAN DALAM CERITA RAKYAT SI KUSUK RAMBUT PANJANG DAN PUTI PENATIH LAILO BARUJI - Mutia Lestari Zurhaz (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2017)
The purpose of this study is to inventory the folklore of the district merangin and analyze the characteristics of female characters in the story of Si Kusuk Hair Panjang and Puti coach lailo baruji. The method used is the method of recording and qualitative descriptive method. The place of research will be conducted in Merangin District in Bangko City, Air Batu Village, Mampun Village, and Tuo Village. The results showed that the researchers managed to inventory ten folklore. Of the ten folklore obtained there are only two folklore which spread also in four village of Merangin namely Sikusuk Rambut Panjang and Puti Penatih lailo Baruji story. Based on the results of the analysis shows that the story of Sikusuk Hair Long did not run its role as a wife well and the story of Puti Coach Lailo Baruji shows that he is a figure of exemplary brother for protecting his brothers from danger. The conclusion obtained from both stories is the high work ethic of the two female leaders who symbolize that the female figure of Merangin District should be sampled in the persistence of work.